The Inuit Tapiriit Kanatami II Case and the Protection of Indigenous Peoples' Rights: A Missed Opportunity? ... - Vezzani, Simone (European Papers (www.europeanpapers.eu), 2016)
European Papers - A Journal on Law and Integration, 2016 1(1), 307-318 ... : European Forum Insight of 16 April 2016 ...